Increased Plasma Fibrinogen and Platelet-Aggregates in Type II Hyperlipoproteinaemia - Lowe, G D O; Drummond, Maureen M; Third, Jane L H C; Bremner, W F; Forbes, C D; Prentice, C R M; Lawrie, T D V (Thrombosis and Haemostasis, 1979)
Plasma fibrinogen and platelet-aggregates (method of Wu and Hoak) were measured in 21 patients with familial Type II hyperlipoproteinaemia and 21 matched control subjects. Patients with hyperlipoproteinaemia had increased levels of fibrinogen and platelet- aggregates (p<0.01). Young patients with hyperlipoproteinaemia had prematurely high fibrinogen levels, and the normal rise in fibrinogen during adult life was abolished. There were no statistically significant correlations within the patient group between fibrinogen, platelet-aggregates, and plasma lipids. High fibrinogen and platelet-aggregate levels may play a part in the development of the premature arterial disease associated with Type II hyperlipoproteinaemia, or may be markers of arterial injury.